Optimization and Validation of RP-HPLC-UV/Vis Method for Determination Phenolic Compounds in Several Personal Care Products - Mohammed Akkbik; Zaini Bin Assim; Fasihuddin Badruddin Ahmad (International Journal of Analytical Chemistry)
An HPLC method with ultraviolet-visible spectrophotometry detection has been optimized and validated for the simultaneous determination of phenolic compounds, such as butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) as antioxidants, and octyl methyl cinnamate (OMC) as UVB-filter in several personal care products. The dynamic range was between 1 to 250 mg/L with relative standard deviation less than 0.25% (𝑛=4). Limits of detection for BHA, BHT, and OMC were 0.196, 0.170, and 0.478 mg/L, respectively. While limits of quantification for BHA, BHT, and OMC were 0.593, 0.515, and 1.448 mg/L, respectively. The recovery for BHA, BHT, and OMC was ranged from 92.1–105.9%, 83.2–108.9%, and 87.3–103.7%, respectively. The concentration ranges of BHA, BHT, and OMC in 12 commercial personal care samples were 0.13–4.85, 0.16–2.30, and 0.12–65.5 mg/g, respectively. The concentrations of phenolic compounds in these personal care samples were below than maximum allowable concentration in personal care formulation, that is, 0.0004–10 mg/g, 0.002–5 mg/g, and up to 100 mg/g for BHA, BHT, and OMC, respectively.